Co-occurrence of autoimmune diseases and metabolic disorders in familial mediterranean fever patients: review of literature and case reports - Chaaban, Ahlam; Baalbaki, Nohad; Narch, Ralph; Eldawra, Eliana; Kobeissy, Philippe Hussein; Ibrahim, José-Noel (Frontiers in Immunology, 2025)
Familial Mediterranean Fever (FMF) is an autosomal recessive autoinflammatory disease predominantly affecting populations from the Mediterranean region, with a high prevalence reported among Armenians, Turks, Arabs, and Jews. The condition results from mutations in the MEFV gene, which encodes pyrin, a key regulator of inflammation. Both genetic and epigenetic factors contribute to the diverse clinical manifestations of FMF, which are characterized by recurrent episodes of fever, abdominal pain, chest pain, arthritis, and erysipelas-like erythema. In addition to these symptoms, individuals with FMF patients appear to have an increased risk of developing autoimmune and metabolic disorders, likely due to shared inflammatory pathways. In fact, FMF exemplifies a monogenic autoinflammatory disorder arising from mutations in genes related to the innate immune system, unlike autoimmune diseases that stem from defects in the adaptive immune system. Despite differences in their underlying mechanisms, both autoinflammatory and autoimmune diseases involve the production of interleukin-1β, a key cytokine that influences effector cells of the adaptive immune system, including B and T lymphocytes. Accordingly, numerous studies have investigated the increased prevalence of autoimmune and metabolic disorders among FMF patients, seeking to understand whether these comorbidities exacerbate FMF symptoms, increase the risk of complications, or affect treatment responses. This review examines the coexistence of FMF with autoimmune diseases and metabolic disorders and explores potential correlations with MEFV mutations.